A methodology for the effective use of materials in concrete paving block. Issue 1 (March 2021) - Edayadiyil, J B; Mathew, S; Joy, M
Abstract: For a long time, concrete paving blocks have been broadly utilized in different countries as a specialized problem-solving technique to provide pavement in areas where, traditional forms of construction were less robust due to several drawbacks. Low maintenance, ease of placing and evacuation and quick use after installation make it best fit for various utilizations where the conventional pavement technologies are not practical or desirable. So there emerges a dynamic enthusiasm for the concepts of the mix design process for the development of concrete paving blocks arises. This paper aims to develop an optimized mix design for concrete paver blocks for medium traffic as per relevant codes, considering quality and economy. To maximise the particle packing density of concrete, the packing density approach was used here. The method of packing density receipt maximises the concrete material packing density by selecting the perfect measure of different aggregates to fill the voids, allowing a denser and firmer structure. The higher degree of particle packing contributes to minimum voids, maximum density, and thus fewer cement and water demands, leading ideal medium traffic design.